Incidence and risk factors of calcium channel blocker–related edema in hypertensive patients: A Multicenter retrospective cohort study - Koricho Simie Tolla; Gashaw Solela; Getachew Wondafrash; Abay Burusie; Gebi Agero; Dureti Desta Garoma; Wubshet Abraham Alemu; Bereket Sinshaw Engida; Surafel Mekasha Woldeyes; Berhanu Moges Abera; Mulualem Alemayehu Gebreselassie (PLoS ONE, 2026)
Background Hypertension is a major risk factor for cardiovascular disease and remains the leading cause of mortality worldwide. Calcium channel blockers (CCBs) are commonly used to lower blood pressure because they are effective and affordable. However, CCBs can cause vasodilatory adverse effects, including peripheral edema, which may lead to additional therapy and affect adherence. This study assessed the incidence and risk factors of CCB-related edema among hypertensive patients in Ethiopia. Methods This retrospective multicenter cohort study involved interviews and reviews of medical records of adults (aged ≥18 years) with essential hypertension who were prescribed calcium channel blockers (CCBs) between July 15 and August 14, 2025. A total of 292 participants were selected using systematic random sampling. A structured questionnaire was used to collect sociodemographic and clinical data. Descriptive statistics summarized baseline characteristics. Time-to-event analysis with the log-rank test assessed the duration from CCB initiation to edema onset. Binary and multivariate logistic regression analyses identified factors associated with CCB-related edema, and a p -value <0.05 was considered statistically significant. Results Among 292 participants (mean age 58.2 years; 53.4% female), 20.9% had diabetes mellitus and 16.8% had dyslipidemia. Amlodipine was the most frequently prescribed CCB (94.8%). Peripheral edema developed in 38.7% of patients, with a mean onset time of 8.3 weeks. In multivariate logistic regression analysis, only longer daily standing duration was significantly associated with edema (AOR = 1.92; 95% confidence interval: 1.03–3.58; p = 0.041). Time-to-event analysis showed a progressive increase in edema risk with continued CCB use. Patients receiving amlodipine 10 mg daily had a greater (42.5% vs. 33%) and earlier risk of edema than those on 5 mg amlodipine daily (log-rank p = 0.003). Conclusions Calcium channel blocker–related peripheral edema is common among Ethiopian patients with hypertension and is more likely with higher doses and prolonged daily standing. Clinicians should be aware of its high prevalence to provide effective patient counseling and avoid unnecessary investigations or treatments, such as diuretics.